2021
DOI: 10.3389/fnut.2021.712600
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin and Circulating Metabolites and Risk of Venous Thromboembolism: A Two-Sample Mendelian Randomization Study

Abstract: Background and Aim: Previous observational studies indicated that the serum albumin levels and circulating metabolites are associated with a high risk of venous thromboembolism (VTE). However, whether these observations reflect causality remained unclear. Hence, we conducted a two-sample Mendelian randomization (MR) analysis to evaluate the causal associations of serum albumin and circulating metabolites with the risk of VTE.Methods and Results: Summary statistics of genetic instruments proxying serum albumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…They found that decreased serum albumin levels in cancer patients were significantly associated with an increased risk of VTE and mortality 29 . Another two-sample mendelian randomization study also indicated that genetic liability to low-serum albumin and total protein levels is associated with a higher risk of VTE 41 . Additionally, hepatic dysfunction, from obstruction of the suprahepatic IVC, or Budd-Chiari syndrome, is known to occur in some RT patients who have advanced IVCTT 42 , leading to serum albumin synthesis disorder and facilitating the vicious circle further.…”
Section: Discussionmentioning
confidence: 97%
“…They found that decreased serum albumin levels in cancer patients were significantly associated with an increased risk of VTE and mortality 29 . Another two-sample mendelian randomization study also indicated that genetic liability to low-serum albumin and total protein levels is associated with a higher risk of VTE 41 . Additionally, hepatic dysfunction, from obstruction of the suprahepatic IVC, or Budd-Chiari syndrome, is known to occur in some RT patients who have advanced IVCTT 42 , leading to serum albumin synthesis disorder and facilitating the vicious circle further.…”
Section: Discussionmentioning
confidence: 97%
“…We utilized two large genetic datasets of the SUA to establish robust causal effects, which provided sufficient power to attain a causal inference. Compared to the previous MR analysis in SUA and VTE, 36 our study is unique and specific as it was restricted to individuals of East Asian descent, reducing the potential bias from population stratification. The use of exposure and outcome data from different populations and differences in the instrumental variables may have contributed to the lack of significant causal effect observed in the previous MR study.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed that hs-CRP level was not an important predictor of LAAT/SEC. Previous data has shown that reduction in albumin concentration and the plasma CRP level are inflammatory markers that might result in thrombosis [ 21 23 ]. These contradictory findings showed that besides inflammation, ALB was another major contributor to the LAAT/SEC.…”
Section: Discussionmentioning
confidence: 99%